2018
DOI: 10.1097/iae.0000000000001763
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes After Intravitreal Injections of Conbercept Versus Ranibizumab for the Treatment of Retinopathy of Prematurity

Abstract: Both conbercept and ranibizumab are effective choice for the treatment of ROP. Conbercept is a novel effective treatment strategy for ROP providing a new treatment option for ophthalmologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 26 publications
5
40
1
Order By: Relevance
“…Our inclusion criteria are broader than the screening guideline recommendations in the USA (GA <30 weeks, BW <1500 g) and UK (GA <32 weeks, BW <1500 g)1 22 because severe ROP occurs in more mature and larger infants in China 23 24. The mean PMA for the time of first IVC is 34.2±1.9 weeks and 5.8±1.4 weeks, which is in accordance with 36.6±3.2 PMA by Wu et al and 36.0±2.34 PMA by Huang et al in the study of bevacizumab and ranibizumab treatment for infants with ROP, respectively,25 but slightly earlier than the 38.47±2.72 weeks reported by Jin et al 26. We found that using an IVC injection once, as monotherapy, resulted in the regression of plus disease without recurrence in 83.7% (40/48) of eyes with type 1 ROP and AP-ROP.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our inclusion criteria are broader than the screening guideline recommendations in the USA (GA <30 weeks, BW <1500 g) and UK (GA <32 weeks, BW <1500 g)1 22 because severe ROP occurs in more mature and larger infants in China 23 24. The mean PMA for the time of first IVC is 34.2±1.9 weeks and 5.8±1.4 weeks, which is in accordance with 36.6±3.2 PMA by Wu et al and 36.0±2.34 PMA by Huang et al in the study of bevacizumab and ranibizumab treatment for infants with ROP, respectively,25 but slightly earlier than the 38.47±2.72 weeks reported by Jin et al 26. We found that using an IVC injection once, as monotherapy, resulted in the regression of plus disease without recurrence in 83.7% (40/48) of eyes with type 1 ROP and AP-ROP.…”
Section: Discussionsupporting
confidence: 88%
“…We found that using an IVC injection once, as monotherapy, resulted in the regression of plus disease without recurrence in 83.7% (40/48) of eyes with type 1 ROP and AP-ROP. This result bore a resemblance to the recently reported regression rate of 85% by Jin et al 26. Similarly, the regression rates are 83.3% by the bevacizumab treatment and 79.5% by ranibizumab treatment, respectively 2 10 21…”
Section: Discussionsupporting
confidence: 86%
“…Y.) according to our preferred technique as previously described [10]. e clinical data and fluorescein angiograms were collected during routine care of the children.…”
Section: Methodsmentioning
confidence: 99%
“…But the side effect of this treatment including visual field loss caused by permanent ablation of the hypoxic retina and subsequent high myopia should not be ignored [7,8]. e off-label intravitreal injection of anti-VEGF agents such as conbercept (KH902; Chengdu Kanghong Biotech Co, Ltd, Sichuan, China), bevacizumab (Genentech, Inc, South San Francisco, CA), ranibizumab (Genentech, Inc and Novartis International AG, Basel, Switzerland), and aflibercept (Regeneron Pharmaceuticals Inc) for ROP treatment has been reported in recent years and shown to be efficacious [9][10][11][12][13]. For most ROP infants, anti-VEGF drugs could effectively improve the structural outcomes in no shorter than 6-month follow-up period although some recurrences may occur in 2.8%-35.7% of them [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation